Environmental heterogeneity shapes the C and S cycling-associated microbial community in Haima's cold seeps - Chen, Yu; Dai, Tianjiao; Li, Niu; Li, Qiqi; Lyu, Yuanjiao; Di, Pengfei; Lyu, Lina; Zhang, Si; Li, Jie (Frontiers in Microbiology, 2023)
Environmental heterogeneity in cold seeps is usually reflected by different inhabiting faunal aggregates. Sediment microbiome, especially the geochemical cycling associated communities, sustains the ecosystem by chemosynthesis. To date, few studies have paid attention to the structuring and functioning of geochemical cycling associated communities relating to environmental heterogeneity in different faunal aggregates of cold seeps. In this study, we profiled the microbial community of four faunal aggregates in Haima cold seep, South China Sea. Through a combination of geochemical and meta-omics approaches, we found that geochemical variables, such as sulfate and calcium, exhibited significant variation between different aggregates, inferring the change of methane flux. Anaerobic methanotrophic archaea (ANME), sulfate reducing and sulfide oxidizing bacteria (SRB and SOB) dominated the microbial community but varied in composition among the four aggregates. Diversity of archaea and bacteria exhibited strong correlation to sulfate, calcium, and silicate. Interspecies co-exclusion inferred by molecular ecological network analysis increased from non-seep to clam aggregate and peaked at mussel aggregate. The networked geochemical cycling associated species showed obvious aggregate-specific distribution pattern. Notably, hydrocarbon oxidation and sulfate reduction by ANME and SRB produced carbonate and sulfide, driving alkalization of sediment environment which may impact on the microbial communities. Collectively, these results highlighted that geofluid and microbial metabolism together resulted in environmental heterogeneity, which shaped the C and S cycling associated microbial community.